INTERNATIONAL MISCARRIAGE RATES: A COMPREHENSIVE OVERVIEW OF PREVALENCE AND CAUSES - Mira Hristova; Mariya Angelova (Peytchinski Publishing, 2024)
Purpose: This research and analysis seek to determine the frequency and total number of miscarriages among women of reproductive age over a span of six years in MBAL "NiaMed", locally and globally. Material/Methods: In an observational study, researchers collected data from scientific articles and workplace sources to investigate miscarriages. The study concentrated on women of reproductive age who had experienced pregnancy-related issues, with all information derived from scientific literature and medical records. Results: Both locally and globally, the incidence of spontaneous abortions remains high despite advances in medical prophylaxis and prevention of reproductive failures. The rates per 1,000 women are 53.7 in Russia, 33 in Mexico, and 11.9 in Bulgaria. This is compared with the local incidence at MBAL "NiaMed" among women who have had two or more miscarriages. Conclusion: Miscarriages represent a major global health concern, impacting millions of women annually. Identifying risk factors and implementing effective interventions can decrease miscarriage rates and enhance pregnancy outcomes. Essential components of a comprehensive strategy to tackle this issue include public health initiatives, better access to healthcare services, and ongoing research into potential treatments.